Teaching Domestic Violence Online: A Step Forward or a Step Backward?. (October 2016) - Danis, Fran S.
With the increasing number of courses and degree programs available online, faculty may be interested in developing an online course on domestic violence. This article analyzes the similarities and differences involved in teaching about domestic violence online versus face-to-face. Highlights of course activities and notable online resources are identified including YouTube videos, webinars, online training modules, and websites. The limitations and challenges of teaching domestic violence in an asynchronous online course and recommendations for future teaching are discussed.